Enhancing flood disaster management in Klang Valley - Mohd Amizan Mohamed,; Abdul Qayyum Mohd Zaman,; Kajewski, Stephen; Bambang Trigunarsyah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Klang Valley, encompassing Kuala Lumpur and Selangor, faces recurrent flooding due to rapid urbanisation and inadequate drainage systems, particularly during monsoon seasons. This research aims to develop a comprehensive framework for enhancing regional flood disaster management. Data were collected from 255 civil engineering professionals through an online survey, with descriptive statistics used to analyse the challenges, practical solutions, and stakeholder roles in managing floods. Key findings highlight that rapid urbanisation and insufficient drainage infrastructure significantly contribute to flood vulnerability. Respondents rated floods as one of Malaysia’s most common natural disasters, with a mean score of 3.90, while lack of public awareness on flood preparedness scored lower at 3.77. Comprehensive urban planning was identified as the most effective solution (mean score of 3.88), followed by investing in drainage infrastructure (mean of 3.73). The study underscores the need for centralised coordination among stakeholders, receiving strong support with a mean score of 3.87. The proposed framework integrates three key phases: mitigation, focusing on urban planning and infrastructure improvements; preparedness, which involves enhancing public awareness and emergency response systems; and response/recovery, ensuring effective crisis management and long-term rehabilitation. The framework emphasises collaboration between government agencies, local authorities, and communities to enhance flood resilience. This research provides valuable insights for developing sustainable, long-term strategies for flood disaster management in the Klang Valley, addressing the challenges posed by urbanisation, climate change, and infrastructure limitations